Alloimmune Responses and Atherosclerotic Disease After Kidney Transplantation. Issue 1 (January 2015) - Ducloux, Didier; Courivaud, Cécile; Bamoulid, Jamal; Bisaccia, Vincent; Roubiou, Caroline; Crepin, Thomas; Gaugler, Béatrice; Laheurte, Caroline; Rebibou, Jean-Michel; Chalopin, Jean-Marc; Saas, Philippe
<x xml:space="preserve">Abstract</x> Background Chronic exposure to exogenous antigens causes accumulation of proinflammatory CD57+CD28− hyperactivated CD8+ T cells that may promote atherosclerosis. We hypothesized that persistent alloimmune responses may induce immune activation and contribute to posttransplant atherosclerosis. Methods This hypothesis was tested in a single-center cohort of 577 kidney transplant patients. Propensity score analysis was performed to address potential confounding variables by indication. Immune exhaustion was studied in subcohort of 103 patients. Results Five hundred seventy-seven consecutive renal transplant recipients were included. Seventy-seven atherosclerotic events (AE) (12.3%) occurred during a mean follow-up of 7 years. The cumulative incidence of AE increased with the number of human leukocyte antigen (HLA) mismatches (18%, 10%, and 5% in patients with 5–6, 3–4, and 0–2 mismatches, respectively; P=0.012). Human leukocyte antigen mismatch number (hazards ratio, 1.35; 95% confidence interval, 1.10–1.66, for each supplementary mismatch; P=0.005) was an independent risk factor for AE. In the propensity score match analysis, having received a well-matched kidney conferred a reduced risk of AE (hazards ratio, 0.22; 95% confidence interval, 0.05–0.95; P=0.044). We observed a significant correlation between HLA mismatch numbers and circulating CD57+CD28− CD8+ T cells (R=0.31; P=0.017). These CD8+ T cells were more frequent in patients with more HLA mismatches (P<0.0001). Conclusion Overall, our results suggest that chronic allogeneic stimulation participates to accelerated atherosclerosis observed after transplantation.